2014
DOI: 10.3382/ps.2013-03427
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of chlorine and thiamine dilauryl sulfate on reduction of Listeria monocytogenes in chicken breast and development of predictive growth models

Abstract: The inhibitory effect of chlorine (50, 100, and 200 mL/kg) and thiamine dilauryl sulfate (TDS: 100, 500, and 1,000 mg/kg) on Listeria monocytogenes in chicken breast was investigated. Also, predictive growth models as a function of chlorine and TDS concentration, and storage temperature (4, 10, and 15°C) were developed using a polynomial model. Listeria monocytogenes counts were significantly (P < 0.05) different in samples treated with sterile distilled water and combinations of chlorine and TDS. The maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Another study made by Tsai et al (1992) indicated that 40 ppm chlorine reduced L. monocytogenes in poultry by only 37% to 50% in 3 to 5 min. Lower reduction in L. monocytogenes count was achieved by Oh et al (2014), where the bacterial populations were reduced by 0.03, 0.06, and 0.22 log cfu/g after treatments of 50 ppm, 100 ppm, and 200 ppm chlorine. At the cell membrane level, TSP at a high pH (pH 12) helps to remove fat films and exerts surfactant or detergent effect.…”
Section: Discussionmentioning
confidence: 93%
“…Another study made by Tsai et al (1992) indicated that 40 ppm chlorine reduced L. monocytogenes in poultry by only 37% to 50% in 3 to 5 min. Lower reduction in L. monocytogenes count was achieved by Oh et al (2014), where the bacterial populations were reduced by 0.03, 0.06, and 0.22 log cfu/g after treatments of 50 ppm, 100 ppm, and 200 ppm chlorine. At the cell membrane level, TSP at a high pH (pH 12) helps to remove fat films and exerts surfactant or detergent effect.…”
Section: Discussionmentioning
confidence: 93%
“…Fransisca and Feng [21] reported the inactivation of E. coli O157:H7 in alfalfa, broccoli, and radish seeds using TDS. Many other researchers have reported synergistic effect of TDS with other chemicals such as malic acid, hydrogen peroxide, and chlorine in various foods [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results of APC reduction were reported by Whyte et al (2001) where dipping by 25 ppm chlorine solution reduce total viable count (TVCs) from 4.98±0.38 to 4.52±0.24 log10 cfu/g, reduced APC by 0.4 log cfu/g, (Gelis and Kabul, 2006) where chlorine reduced APC by 0.3 log cfu/g. Moreover, lower reduction of APC reported by EL dosoky and Sherins (2012) where treatment by 25ppm and 50ppm chlorine solution caused reduction by 0.02 and 0.11 log cfu/g, respectively, (Oh et al, 2014) where the APC were reduced by 0.03, 0.06, and 0.22 log cfu/g after treatments of 50 ppm, 100 ppm, and 200 ppm chlorine solution. Comparatively higher reduction of APC obtained by Bautista et al (1995) when used 50ppm chlorine solution caused reduction of APC by 2.4 log cfu/g.…”
Section: Discussionmentioning
confidence: 73%